Comparative Genomic Hybridization Detects An Increased Number of Chromosomal Alterations in Large Cell/Anaplastic Medulloblastomas - Charles G. Eberhart; John Kratz; Amy E. Schuster; Pat Goldthwaite; Kenneth J. Cohen; Elizabeth J. Perlman; Peter C. Burger (2002)
We correlate chromosomal changes in medulloblastomas with histologic subtype, reporting the analysis of 33 medulloblastoma specimens by comparative genomic hybridization, and a subset by fluorescence in situ hybridization. Of the 33 tumors, 5 were desmoplastic/nodular, 10 were histologically classic, and 18 were large cell/anaplastic. Chromosomal gains and losses were more common in anaplastic medulloblastomas than in non-anaplastic ones. We identified 4 medulloblastomas with c-myc amplification and 5 medulloblastomas with N-myc amplification; all 9 were of the large cell/anaplastic subtype. Additional regions with high level gains included 2q14-22, 3p23, 5p14-pter, 8q24, 9p22-23, 10p12-pter, 12q24, 12p11-12, 17p11-12, and Xp11. The majority of these high level gains occurred in anaplastic cases. We also found loss of chromosome 17p in 7 large cell/anaplastic cases but no nonanaplastic medulloblastomas. Finally, we detected a significantly increased overall number of chromosomal alterations in large cell/anaplastic medulloblastomas (6.8/case) compared to non-anaplastic ones (3.3/case). These findings support an association between myc oncogene amplification, 17p loss, and large cell/anaplastic histology.